(untitled) (Research, Society and Development, 2024)
The green banana flour (GBF) is a functional food rich in resistant starch and nutrients, probiotic, and has low glycemic index. The obtaining of the flour is usually done in dryers with high energy consumption, and possible deteriorating processes. These problems can be minimized with an adaptive temperature control system in infrared heat sources. The aim of this research was to quantify the energy savings in the production of green banana flour produced by infrared drying compared to the conventional process of drying in a resistance oven. The production of flour from green banana pulp was evaluated using an infrared radiation dryer with fruit surface temperature control (IR-FSTC). The IR-FSTC was performed by keeping the pulp surface at 50 °C and 60 °C. The results were compared with conventional drying using a resistive source. The energy consumption of drying using IR-FSTC was significantly reduced compared to the drying by resistive source and prevented the formation of hotspots. The drying process was also evaluated by physicochemical and spectroscopic analyses of the GBF. The product maintained the pH, titratable acidity, total soluble solids, and lipid content with values similar to those obtained by conventional heating oven drying. In turn, the spectroscopic analyses confirmed the maintenance of biomolecules inherent in GBF. Thus, it is concluded that the results contribute to the sustainable use of energy resources in the production of GBF.